AN ANALYSIS OF THE CHARACTERIZATION OF THE CHARACTERS IN SHORT MOVIE ENTITLED IBU - Dita Aulia Rahmah; Mutmainah Mustofa; Izzatin Nisa' (Universitas Muhammadiyah Gorontalo, 2021)
ABSTRACTCharacter is someone who appears in the story such as in short stories, novels, dramas, or movies. In this research, the researcher would like to analyze the characterization of the characters in the short movie entitled IBU. The research problems of this research are 1). How is the characterization of the characters? 2). What moral value that we got from the movie?. The purpose of this research is to know the characterization of the characters and to know the moral values that can we get. This research used qualitative descriptive to analyze and interpret the research object in the short movie entitled IBU. The researchers used table analysis in collecting the data. After that, the researchers explain and describe the result based on the table and made a conclusion. Based on the result, the researcher found the characterization of the characters. It is found that Gerry was an antagonist character while the mother was a protagonist character.